Targeted modifications of monolithic multiterminal superconducting weak-links. Issue 14 (24th March 2022) - Collienne, Simon; Majidi, Danial; Van de Vondel, Joris; Winkelmann, Clemens B.; Silhanek, Alejandro V.
Abstract : Targeted modifications of the material properties by properly selecting the intensity and polarity of the applied current in a Y-shape multiterminal device made of superconducting Nb on sapphire. Abstract : In a multi-branch metallic interconnect we demonstrate the possibility to induce targeted modifications of the material properties by properly selecting the intensity and polarity of the applied current. We illustrate this effect in Y-shape multiterminal devices made of Nb on sapphire for which we show that the superconducting critical current can be lowered in a controlled manner at a preselected junction. We further observe the gradual appearance of Fraunhofer-like critical current oscillations with magnetic field which indicates the gradual modification of a superconducting weak link. This method permits progressive modifications of a hand-picked junction without affecting the neighboring terminals. The proposed approach has the benefit of being inexpensive and requiring conventional electronics. This technique represents a major step toward all-electric control of multiterminal Josephson junctions.